Assembly of NHC-stabilized 2-hydrophosphasilenes from Si(iv) precursors: a Lewis acid–base complex. Issue 48 (22nd November 2016) - Dhara, Debabrata; Mandal, Debdeep; Maiti, Avijit; Yildiz, Cem B.; Kalita, Pankaj; Chrysochos, Nicolas; Schulzke, Carola; Chandrasekhar, Vadapalli; Jana, Anukul
Abstract : Reaction of an aryldichlorosilane with lithiumarylphosphide leads to 1, 2-dihydro-2-chlorophosphasilane which yields NHC-stabilized 2-hydrophosphasilene upon NHC-assisted elimination of HCl. Abstract : NHC-stabilized 2-hydrophosphasilenes are obtained from 1, 2-dihydro-2-chlorophosphasilanes as Si(iv ) precursors by a NHC-assisted 1, 2-elimination of HCl. The NHC-exchange of these compounds is demonstrated as a proof of donor acceptor bonding between NHC and the silicon centre of the "SiP" moiety. We have also explored the possibility of similar exchanges in NHC-stabilized Si2 and P2 compounds. Theoretical DFT calculations were performed to address the nature of Si–P bonding in the NHC-stabilized 2-hydrophosphasilenes.